2022
DOI: 10.1097/ee9.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Exposomic determinants of immune-mediated diseases

Abstract: The incidence of immune-mediated diseases (IMDs) is increasing rapidly in the developed countries constituting a huge medical, economic, and societal challenge. The exposome plays an important role since genetic factors cannot explain such a rapid change. In the Human Exposomic Determinants of Immune Mediated Diseases (HEDIMED) project, altogether 22 academic and industrial partners join their multidisciplinary forces to identify exposomic determinants that are driving the IMD epidemic. The project is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…The rationale in the first part of this approach is that after careful mixing and sieving, the frequency of potentially harmful agents is too low to cause an infection or toxification (Braciale et al., 2012; Paludan et al., 2021; Taylor & Latham, 2001). This finding facilitated human trials with homogenized soil that was shown safe for adults (Nurminen et al., 2018), 3‐ to 5‐year‐old children (Roslund et al., 2022) and ongoing trial with infants (Laiho et al., 2022). As stated earlier, these trials did not contain intentional soil eating.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The rationale in the first part of this approach is that after careful mixing and sieving, the frequency of potentially harmful agents is too low to cause an infection or toxification (Braciale et al., 2012; Paludan et al., 2021; Taylor & Latham, 2001). This finding facilitated human trials with homogenized soil that was shown safe for adults (Nurminen et al., 2018), 3‐ to 5‐year‐old children (Roslund et al., 2022) and ongoing trial with infants (Laiho et al., 2022). As stated earlier, these trials did not contain intentional soil eating.…”
Section: Discussionmentioning
confidence: 92%
“…3-to 5-year-old children (Roslund et al, 2022) and ongoing trial with infants (Laiho et al, 2022). As stated earlier, these trials did not contain intentional soil eating.…”
Section: Future Approaches and Limitationsmentioning
confidence: 99%
“…The incidence of immune-mediated disorders such as allergies is on a consistent rise [ 1 , 2 ]. Yet, there remains a significant gap in our understanding regarding the interplay of various factors such as genetic predisposition, exposures during prenatal and postnatal life, and environmental influences in the initiation and progression of these conditions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%